Exploring the effectiveness of project-based learning on students’ motivation in science: An action research study - Dhitareka, Putra Habib; Nuraeni, Selvi; Winarno, Nanang; Sriyati, Siti; Supriyatin, Titin (Jurnal Kajian Pendidikan IPA, 2025)
This study aims to examine the effect of project-based learning (PjBL) on students’ motivation in science learning. The participants consisted of 31 eighth-grade students from a public school in Bandung, West Java, comprising 16 male and 15 female students. The research employed a classroom action research design, with data collected through questionnaires and classroom observations. Specifically, students’ motivation was measured using the Students’ Motivation Toward Science Learning (SMTSL) questionnaire, which encompasses six dimensions: self-efficacy, active learning strategies, science learning value, performance goal, achievement goal, and learning environment stimulation. The findings revealed that students’ motivation levels in science learning during Cycle 1 and Cycle 2 were 69% and 68%, respectively, both categorized as “good.” However, the data also indicated a lack of significant improvement in motivation despite the implementation of the PjBL approach. This stagnation suggests that further exploration is needed to understand the underlying factors contributing to the limited impact of PjBL on students' motivational development. Potential areas of inquiry include the quality of project implementation, student engagement dynamics, and contextual factors within the learning environment that may have influenced the outcomes. Key word: Action Research, Project-Based Learning, Students’ Motivation, Science Learning